Chest compression release velocity factors during out-of-hospital cardiac resuscitation - Beger, Samuel; Sutter, John; Vadeboncoeur, Tyler; Silver, Annemarie; Hu, Chengcheng; Spaite, Daniel W.; Bobrow, Bentley (Resuscitation, 2019)
Higher chest compression release velocity (CCRV) has been associated with better outcomes after out-of-hospital cardiac arrest (OHCA), and patient factors have been associated with variations in chest wall compliance and compressibility. We evaluated whether patient sex, age, weight, and time in resuscitation were associated with CCRV during pre-hospital resuscitation from OHCA. Observational study of prospectively collected OHCA quality improvement data in two suburban EMS agencies in Arizona between 10/1/2008 and 12/31/2016. Subject-level mean CCRV during the first 10 min of compressions was correlated with categorical variables by the Wilcoxon rank-sum test and with continuous variables by the Spearman’s rank correlation coefficient. Generalized estimating equation and linear mixed-effect models were used to study the trend of CCRV over time. During the study period, 2535 adult OHCA cases were treated. After exclusion criteria, 1140 cases remained for analysis. Median duration of recorded compressions was 8.70 min during the first 10 min of CPR. An overall decline in CCRV was observed even after adjusting for compression depth. The subject-level mean CCRV was higher for minutes 0–5 than for minutes 5–10 (mean 347.9 mm/s vs. 339.0 mm/s, 95% CI of the difference −12.4 to −5.4, p < 0.0001). Males exhibited a greater mean CCRV compared to females [344.4 mm/s (IQR 307.3–384.6) vs. 331.5 mm/s (IQR 285.3–385.5), p = 0.013]. Mean CCRV was negatively correlated with age and positively correlated with patient weight. CCRV declines significantly over the course of resuscitation. Patient characteristics including male sex, younger age, and increased weight were associated with a higher CCRV.